# Simplify -5(1-x)-3(x+1)

### 4 Answers | Add Yours

-5(1-x) - 3(x+1)

First we will open the brackets by multiplying the constants.

==> -5*1 - 5*-x -3*x -3*1

==> -5 + 5x -3x -3

Now we will combine terms.

==> (5x-3x) -5-3

==> 2x -8

**Then, the simplest form is (2x-8).**

**-5(1-x)-3(x+1)**

First open the barackets (keeping the mathematical conventions in mind that 2 or more operators cannot be combined) as under:

= -5*1 -5(-x) -3*x -3*1

= -5 + 5x -3x -3

re-arrange similar terms (putting the variables first and then constants) and simplyfy:

= +5x - 3x - 5 - 3

= **2x - 8** ....... and this is the simplest form

## -5(1-x)-3(x+1)

= -5+5x + -3x -3

= -5 + 2x - 3

=-8 +2x

= 2x-8

The expression to be simplified is -5(1-x)-3(x+1)

-5(1-x)-3(x+1)

open the brackets

=> -5 + 5x - 3x - 3

=> 5x - 3x - 5 - 3

=> 2x - 8

**The required simplified form is 2x - 8**